Burkina Faso Priorities for Poverty Reduction and Shared Prosperity : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2017)
The rate of Burkina Faso’s progress towards the eradication of extreme poverty and the reduction of inequalities over recent years has been sub-optimal. This Systematic Country Diagnostic (SCD) is an analytical report prepared by the World Bank Group (WBG) in an attempt to identify and analyze the factors that can help Burkina Faso accelerate its quest towards the achievement of the twin goals of reduced poverty and shared prosperity. The SCD assesses Burkina Faso’s performance in order to identify the constraints and to formulate a set of key priorities to facilitate the achievement of these goals. By focusing on the most significant issues affecting theachievement of these goals, the SCD is intended to inform the formulation of the upcoming Country Partnership Framework (CPF) and thus to facilitate the optimization of the WBG’s assistance to Burkina Faso. The SCD is organized in three parts. Part One establishes a context for the analysis through an assessment of the state of Burkina Faso’s economy and the progress it has made towards the achievement of the twin goals of poverty eradication and shared prosperity. Part Two presents a unified analytical framework to identity the main constraints on the lack of Burkina Faso’s progress towards the achievement of these goals. This framework focuses on two key constraints, these being the limited extent to which productive jobs have been created and the limited degree of access by poor households to a minimal package of services and infrastructure. Part Three attempts to rank policy priorities in the context of the analysis of the key constraints, international experience, and the perceptions of key stakeholder groups in Burkina Faso.